An Investigation on the High-Temperature Stability and Tribological Properties of Impregnated Graphite - Juying Zhao; Qi Xin; Yunshuang Pang; Xiao Ning; Lingcheng Kong; Guangyang Hu; Ying Liu; Haosheng Chen; Yongjian Li (Lubricants)
Impregnated graphite is a common material for friction pairs in aeroengine seals, especially at high temperatures. For the convenience of the application of graphite materials in aeroengines, an SRV-4 tribometer and a synchronous thermal analyzer are employed to study the tribological properties and thermal stability of pure, resin-impregnated, metal-impregnated, and phosphate-impregnated graphite against stainless steel from room temperature to 500 °C. The results indicate that impregnations can improve the wear resistance and thermal stability of graphite at high temperatures. Compared with other impregnated graphite materials, the resin-impregnated graphite shows a good friction coefficient and poor wear rate and thermal stability over 300 °C, due to the degradation and oxidation of the resin-and-graphite matrix. The metal- and phosphate-impregnated graphite materials exhibit excellent wear resistance and thermal stability under 500 °C as a result of the protection of the impregnations, while the average friction coefficient of the metal-impregnated graphite is much greater than the phosphate-impregnated graphite, and even reaches 2.14-fold at 300 °C. The wear rates for the graphite impregnated with resin, metal, and phosphate are 235 × 10−7, 7 × 10−7, and 16 × 10−7 mm3N−1m−1 at 500 °C, respectively. Considering all aspects, the phosphate-impregnated graphite exhibits excellent tribological properties and thermal stability.